Predikce sekundární struktury proteinů s využitím neuronových sítí - Šamšula, Radek (Vysoké učení technické v Brně. Fakulta informačních technologií, 2012)
Bakalářská práce se zabývá problematikou neuronových sítí a predikcí sekundární struktury proteinů. Blíže se zaměřuje na vícevrstvé neuronové sítě s učícím algoritmem zpětného šíření chyby a na jejich použití pro predikci. Je zkoumán vliv architektury sítě a nastavení jejich parametrů na výslednou predikci. Dále je diskutována vhodnost použití této sítě pro tento druh predikce.

Bachelor's thesis studies the problems of neural networks and prediction of protein secondary structure. This thesis is focused on multilayer neural network with back-propagation learning algorithm and their use for prediction. It describes the infuence of network architecture and their parameters settings on the prediction results. Furthermore suitability of the network for this kind of prediction is discused.
Neural Networks for Protein Structure Predictions
Keywords: Neuron; neuronová síť; predikce; backpropagation; struktura proteinu.; Neuron; neural network; prediction; backpropagation; protein structure.